ASSEMBLING AND TESTING AN AMATEUR RADIO RECEIVER - Odmaa Luvsan; Munkh-Onon Munkhmandakh (International Journal of Innovative Technologies in Social Science, 2025)
American artist Samuel Morse (Samuel Finley Breese Morse, 1791.04.27-1872.04.02) conceived and documented his concept for a communication device that could transmit information over long distances based on the principle of electromagnetic induction, which was discovered by the renowned physicist M. Faraday in 1832 during his voyage back to the United States from England aboard the ship "Sally". In 1837, he constructed his first telegraph and created the Morse code the following year. On September 4, 1837, Morse showcased his invention at New York University, where he met his future assistant Alfred Weil, from a distance of 1,700 feet. The inaugural telegraph message was sent by S. Morse from Washington, D.C. to Baltimore, D.C. on May 24, 1844, at 8:45 a.m. The message, "What Hath God Wrought," traveled over a 37-mile (60 km) wire between the two cities and was received by A. Weil. The message was transcribed as dots and dashes on a paper strip at the receiving end using an ink pen connected to an electromagnet. Morse code was later transmitted audibly using a sound generator. Therefore, Morse code is utilized globally, including by the Armed Forces and military organizations of various countries, as the primary method of communication, information exchange, and transmission. In recent times, amateur radio and radio sports have emerged as a competitive activity, with its origins traced back to Northern and Eastern Europe in the late 1950s. The inception of radio sports in Mongolia dates back to April 15, 1958, with the formation of the Radio Central Club.